Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1126/sciadv.abo0732
|View full text |Cite|
|
Sign up to set email alerts
|

Differential proinflammatory activities of Spike proteins of SARS-CoV-2 variants of concern

Abstract: The coronavirus disease 2019 (COVID-19) pandemic turned the whole world upside down in a short time. One of the main challenges faced has been to understand COVID-19–associated life-threatening hyperinflammation, the so-called cytokine storm syndrome (CSS). We report here the proinflammatory role of Spike (S) proteins from different severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants of concern in zebrafish. We found that wild-type/Wuhan variant S1 (S1WT) promoted neutrophil and macrophage re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…Thus, the forced expression of full-length wild type S led to the induction of strong inflammation and generation of hemorrhages in the head of about 45% of the larvae, confirming the proinflammatory effects of wild type S in zebrafish larvae (Tyrkalska et al. 2022 ).…”
Section: Zebrafish Models Of Covid-19supporting
confidence: 61%
See 2 more Smart Citations
“…Thus, the forced expression of full-length wild type S led to the induction of strong inflammation and generation of hemorrhages in the head of about 45% of the larvae, confirming the proinflammatory effects of wild type S in zebrafish larvae (Tyrkalska et al. 2022 ).…”
Section: Zebrafish Models Of Covid-19supporting
confidence: 61%
“…Our group has very recently shown that S1 domain of recombinant S protein (S1WT) can provoke local and systemic inflammation, CRS, emergency myelopoiesis, strong recruitment of the immune cells to the site of the protein injection and intracranial hemorrhages in vivo in zebrafish larvae (Tyrkalska et al. 2022 ). Notably, the injection of S1WT into the hindbrain of 48 hours post fertilization (hpf) larvae strongly induced the production of pro-inflammatory cytokines, the production of neutrophils and macrophages in response to the threat, as well as caused hemorrhages in the head of 25% of the larvae.…”
Section: Zebrafish Models Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, and even more important, these studies did not consider the possibility that the SARS-CoV-2 positive individuals enrolled could be infected by distinct SARS-CoV-2 variants. Since it has already been described that the distinct SARS-CoV-2 variants of concern are able to elicit distinct responses in the host [ 79 , 80 ], it would not be surprising if these variants could differentially alter the nasopharyngeal microbiota. This is a particularly relevant issue to consider here, as some of these studies even state that their samples come from three different COVID-19 waves and from patients with different disease severities (Table S1) [ 66 , 67 , 70 ], which makes it very likely that they may be infected by distinct variants of the virus and, therefore, the results from the different patients enrolled in these studies would not be comparable.…”
Section: Changes In the Nasopharyngeal Microbiota Of Sars-cov-2-infec...mentioning
confidence: 99%
“…Severe COVID-19 pneumonia results from a complex impairment of the inflammatory and immune responses against SARS-CoV-2 infection. 4 Both in vitro and in vivo animal model studies have suggested that viral variants differently modulate immunity and/or inflammation pathways, 7,14,19,20,33 possibly explaining differences in their pathogenicity and clinical expression. Differences in their transmissibility and ability to induce severe disease have been suggested by several cohort studies.…”
Section: Discussionmentioning
confidence: 99%